Annual Report on surveillance for avian influenza in poultry and wild birds in Member States of the European Union in 2020. (6th December 2021) - ,; Aznar, Inma; Baldinelli, Francesca; Papanikolaou, Alexandra; Stoicescu, Anca; Van der Stede, Yves
Abstract: In 2020, Council Directive 2005/94/EC required EU Member States (MSs) to carry out surveillance for avian influenza (AI) in poultry and wild birds and notify the results to the responsible authority. Based on this, MSs, Iceland, Norway, Switzerland and the United Kingdom implemented ongoing surveillance programmes to monitor incursions of AI viruses in poultry and wild birds. EFSA received a mandate from the European Commission to collate, validate, analyse and summarise the data resulting from the avian influenza surveillance programmes in an annual report. This is the second such report produced using data directly submitted to EFSA by MSs. This report summarises the results of the surveillance activities carried out in poultry and wild birds in 2020. Overall, 24, 768 poultry establishments (PEs) were sampled, of which 46 were seropositive for H5 virus strains and seven for H7 strains. Seropositive PEs were found in nine MSs (Belgium, Denmark, Finland, France, Italy, the Netherlands, Poland, Spain and Sweden) and the United Kingdom. As per previous years, the highest percentages of seropositive PEs were found in establishments raising waterfowl game birds and breeding geese. Out of the 53 PEs with positive serological tests for H5/H7, seven tested positive in polymerase chain reaction (PCR) or virology for H5/H7 virus strains: six for Low Pathogenic Avian Influenza (LPAI) and one for Highly Pathogenic Avian Influenza (HPAI). In addition, 13 countries also reported PCR results from 748 PEs which did not correspond to the follow‐up testing of a positive serology event (e.g. in some PEs, PCR tests were used for screening). Twenty‐five of these PEs were found positive for AI viral RNA. These positive PEs were located in Bulgaria, Estonia, Germany, Romania and Slovakia. A total of 18, 968 wild birds were sampled, with 878 birds testing positive to HPAI virus. Fourteen countries reported HPAI‐positive wild birds, with all HPAI strains identified as H5. Most positive birds were infected with H5N8, with a smaller number of N1, N3, N5 and unidentified NA subtypes. In addition, there were 317 birds testing positive for LPAI H5 or H7 virus and 429 birds testing positive for non‐H5/H7 AI virus, reported by 31 countries. The surveillance findings for poultry and wild birds for 2020 are discussed in relation to the current knowledge of the epidemiology of AI in Europe, in particular the H5N8 epidemic which has been identified late 2020.